Health self-perception by dementia family caregivers: sociodemographic and clinical factors - Letice Ericeira Valente; Annibal Truzzi; Wanderson F. Souza; Gilberto Sousa Alves; Carlos Eduardo de Oliveira Alves; Felipe Kenji Sudo; Maria Elisa O. Lanna; Denise Madeira Moreira; Eliasz Engelhardt; Jerson Laks (Arquivos de Neuro-Psiquiatria)
Caring for a demented family member has been associated with burden. Studies concerning health self-perception of family caregivers are still scarce. OBJECTIVE: To investigate caregivers perceived health and to look into relationships with patients and caregivers' sociodemographic and clinical data. METHOD: Dyads of dementia outpatients and family caregivers (n=137) were assessed with Mini Mental State Examination, Functional Activities Questionnaire, Neuropsychiatric Inventory and Clinical Dementia Rating. Caregivers answered Sociodemographic Questionnaire, Beck Depression and Anxiety Inventories, Zarit Burden Interview and Maslach Burnout Inventory. RESULTS: Caregivers poor perceived health was associated with emotional exhaustion, burden, depression and anxiety. Logistic regression analyses revealed caregivers' age, anxiety and physical problem as the main predictors of health self-perception. CONCLUSION: Aged family caregivers with anxiety who also report physical problem characterize a group at risk for poor self-perceived health. Evaluation of health self-perception may be useful for designing interventions to improve anxiety and physical health.